Competency of PJOK Teachers in Elementary Schools in East Ungaran District, Semarang Regency - Nurcahyani, Atip; Rahayu, Setya; Hartono, Mugiyo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Basic competence of a good teacher is very important to improve the quality of education in Indonesia, but there are some problems of teacher competence that are very interesting to study and research, especially at the elementary school level. The problem in this research: How is the Pedagogic Competence, Personality Competence, Social Competence and Professional Competence of Physical Education Teachers in Sports and Health in elementary schools in East Ungaran Sub-district, Semarang Regency. The approach in this study is a qualitative research approach using qualitative data analysis techniques with interactive analysis models (Interactive Analysis Models), namely the components of data reduction and data presentation carried out together with the data collection process. After the data is collected, the three components of the analysis (data reduction, data presentation and conclusion drawing) interact with each other. This study uses two supporting data, namely primary data and secondary data. The number of informants is 20 public elementary schools in East Ungaran sub-district. The results of this study are the pedagogical competence of teachers of Physical Education, Sports and Health in the District of East Ungaran in the very good category reaching 10%, 80% good, and 10% sufficient. Personal competence of Physical Education, Sports and Health teachers is 40% in very good category, 50% is good, and 10% is sufficient. Social competence reached 45% very good, 50% good, and 5% enough. Professional competence is 10% very good, 70% good, and 20% quite. The conclusion of the study is that the pedagogic, personality, social and professional competencies of Physical Education and Sports teachers in East Ungaran District are good. Suggestions in this study are that increasing professional competence needs attention so that the quality of education in Indonesia in particular can increase.